2008
DOI: 10.1152/ajpregu.90623.2008
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte migration and cellular stress induced in liver, lung, and intestine during sleep loss and sleep recovery

Abstract: Everson CA, Thalacker CD, Hogg N. Phagocyte migration and cellular stress induced in liver, lung, and intestine during sleep loss and sleep recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 71 publications
3
25
0
2
Order By: Relevance
“…In fact, prolonged periods of sleep deprivation are notorious for promoting neutrophil migration to the extravascular spaces of lung and liver, concomitant with the increased cell stress [16] . Nonetheless, these effects were evident after 5-10 days of total sleep deprivation, indicating again that the effects of sleep deprivation depend on the length and the extent of sleep loss applied (that is, total sleep deprivation vs. PSD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, prolonged periods of sleep deprivation are notorious for promoting neutrophil migration to the extravascular spaces of lung and liver, concomitant with the increased cell stress [16] . Nonetheless, these effects were evident after 5-10 days of total sleep deprivation, indicating again that the effects of sleep deprivation depend on the length and the extent of sleep loss applied (that is, total sleep deprivation vs. PSD).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, experimental sleep deprivation reduced circulating lymphocyte numbers [9][10][11] and decreased the antibody response to hepatitis A vaccination [12] . In rodent studies, Everson and colleagues conducted a number of experiments on rats, demonstrating that total sleep deprivation (SD) increases the invasion of opportunistic bacteria in blood [13] , intestine and mesenteric lymph nodes [14] , concomitant with the increased endotoxin concentrations in serum [15] and increased cell stress [16] .…”
Section: Introductionmentioning
confidence: 99%
“…To produce chronic sleep restriction, the disk was rotated for 6 s according to a pattern of disk rotations that had reliably produced reduced and highly fragmented sleep under acute conditions (23,26). In these prior studies, the housing platform had been rotated for 6 s each time sleep onset was detected in a rat to be totally deprived of sleep, which reduced and fragmented the sleep of a paired rat housed on the same platform.…”
Section: Animals and Environmental Conditionsmentioning
confidence: 99%
“…83). Already well established is the fact that acutely sustained total sleep deprivation in laboratory rats results in a progressive negative energy balance (2, 20, 28), suppression of major anabolic hormones (21, 24), and immune-related abnormalities (18,19,26,27) that turn lethal after an average of 16 to 21 days (20,53,55,62). However, rats that obtain nearly half-normal sleep amounts during the same time period do not develop severe pathology and do not die (20,53,55,62).…”
mentioning
confidence: 99%
“…Another study revealed that three times as many sleep-dependent transcriptional changes occur in the liver relative to the brain, thus suggesting that sleep can selectively affect non-neural tissues [120]. Furthermore, no selective brain pathology has been reported in rats, flies or worms that have been sleep deprived until they die, although those animals showed signs of increased oxidative stress [121, 122]. Lastly, DAF-16/FOXO is required in muscle for normal responses to sleep deprivation in worms [123].…”
Section: Molecular Indicators Of Sleep’s Functionsmentioning
confidence: 99%